British Battalion XV International Brigade / [Philip Bolsover... et al.]. - Bolsover, Philip ; Copeman, Fred, 1907-1983 ; McDade, Alex, 1905-1937 ; Tomalin, Miles ; Green, Nan; Spain. Ejército Popular de la República. Brigada Internacional, XV. (London : Marston)
1939-01 SP01-002-11 80 pages : illustrations ; 18 cm. JD 10.P6 PPC 1724